THE ROLE OF PRODUCT UPDATE ON THE PERFORMANCE OF MARKETING (CASE STUDY OF BANG HASYIM ARJASA FURNITURE) - I Dewa Made Yuda Mahendra (SEAN Institute, 2022)
The desired sales program based on sales research expected by the industry is how to develop total marketing of goods and services on target. The sales program made by the industry is aimed at obtaining work results, especially sales work results. In large industries, renewal of ready-made goods and services. Sales programs made by sustainable market industries are in line with the need to strive to be consistent, not to change from the original situation regarding the results of sales work, but what about for small and medium industries, for example the furniture industry, which still has a dependence on understanding Sales sales program. For small and medium industries, is product renewal a fundamental matter for sustainable business continuity? The part of the population studied in this research was the furniture industry in the Arjasa sub-district, a total of 38 correspondents. The data analysis method used by the reviewers is simple regression analysis. Updates to goods have an impact on the results of sales work, for this reason the industry is focused on maintaining the quality of goods that buyers can rely on.